EFEKTIVITAS PROGRAM USAHA PENINGKATAN PENDAPATAN KELUARGA PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA - Purwana, Krisdanu (CV. Lafadz Jaya, 2024)
The background to the problem in this research is that the problem of poverty continues to be an important problem in Indonesia. Poor people are generally powerless or lack the skills to be able to develop themselves towards a prosperous level. This research aims to determine the effectiveness of business programs to increase family income, empowerment, and family welfare. This research is field research with a descriptive qualitative approach. The research results show that efforts to increase participants' income can be done by improving participants' skills through mentoring, where family planning officers/extension officers can provide guidance and training, so that they can further develop other productive economic businesses. Other efforts can also be made by prioritizing Pre-Prosperous Families (Pra KS) and Prosperous Families I (KS I) as program targets. If the program target is more appropriate for Pre KS and KS I who have a higher work ethic compared to KS II, KS III and KS III+, then the use of aid will also be more appropriate, namely only for productive economic efforts, so that increasing income will be easier achieved.